STRATEGI PENERAPAN MANAJEMEN BERBASIS SEKOLAH (Studi Kasus di MI Nurul Islam Ngaliyan Semarang) - Munif Kholifah Sulistiyoningrum (Kopertais Wilayah X Jawa Tengah, 2016)
AbstractSchool based management determines e? ectiveness, e? ciency and productivity of school organization. It constitutes a new paradigm on educational system that gives wide autonomy to manage human and ? nance resources depending on priority. Its implementation is based on UU No.20 in 2003 regarding national education system article 51. MI Nurul Islam is one of the basic educational institutions that have successfully implemented school-based management. Th is is proved by academic and non-academic outcomes, supported by competitive quality, especially on religious discipline; good implementation stage of school based management (MBS); decentralization of educational implementation and successful character of headmaster of MI Nurul Islam. By using descriptive-qualitative approach, this study tries to explore the implementation strategy of school based management (MBS) in MI Nurul Islam Ngaliyan Semarang.Keywords: School Based Management, Implementation Strategy, MI Nurul Islam, autonomy, decentralization.